A reinvenção da roda: modos de aprender e conhecer de mestras e professoras na prática de pedagogias decoloniais - Carrenho, Natali Seleguim (Universidade Federal de São Carlos, 2023)
The end of the Cold War did not mean the end of colonialism, but it did give rise to coloniality. Laws no. 10.639/2003 and no. 11.645/2008, which deal with the mandatory teaching of African and indigenous cultures in the Brazilian curriculum, are a milestone for the implementation of decolonial practices in schools. However, developing decolonial and anti-racist practices in basic education schools is a challenge for many teachers. The group of teachers involved in this research reported that they did not have these themes in their teaching training. This study intended to investigate how the ways of knowing and learning of masters and teachers are, during the experiences of self-training, for the implementation of decolonial practices. Its specific objectives were: to monitor the involvement of a study group in the implementation of decolonial pedagogy practices in basic education; and to understand the marks in the experiences lived with female teachers while developing practices of oral tradition with basic education teachers from different areas of knowledge. Based on the material produced by the movement of the two analyses, the research question was: what are the masters and teachers’s ways of knowing and perceiving the implementation of practices in decolonial pedagogies in basic education? At the same time, the questioning permeated the researcher's memorial and her teaching practice as a teacher of Culture, Identity and Place, a specific curricular component of comprehensive education schools in the municipal network of Campinas (SP), Brazil. In this way, oral tradition and popular culture became the center of the circle, in a political perspective of curriculum inversion, with ancestry and identity as the focus. The research had a qualitative approach and made use of two instruments: semi-structured interviews with teachers and reflective narratives by teachers. It is an investigation inspired by the sociological perspective, due to the fact that decolonial pedagogy provides popular knowledge and social struggles. The study, as far as possible, sought to break paradigms such as the rigor of scientific language, evidenced the non-hierarchization of curricular components in comprehensive education and, as it took place in a natural environment, considered the narratives of the subjects, contributing to the historical-social erasure. The results indicate that the approach to decolonial pedagogies, during the study group meetings, produced personal and professional inflections in our co-authors. For some, these were the first experiences in experiential classes, as well as meetings with indigenous people and visits to cultural points in the city of Campinas, situations and sharing that in themselves are already knowledge, but also that inspired their teaching practices. Understanding that the ways of knowing and learning of teachers and masters are individual, but they converge to a collective political-pedagogical ideal, it was concluded that it is necessary to educate the look, know how to listen to develop decolonial practices in basic education, and that living practices of oral tradition is fundamental in this process. Such practices must be structured by a decolonial bias and place oppressed people at the center of the circle. That is, what matters is the thought that underlies the practice. This research showed some of these pedagogies and paths to be taken in this regard, based on the experience lived by the co-authors and narrated by the teacher-researcher.
The reinvention of the wheel: ways of knowing and learning by masters and teachers in the practice of decolonial pedagogies
Keywords: Pedagogias decoloniais; Tradição oral; Narrativas reflexivas; Decolonial pedagogies; Oral tradition; Reflective narratives; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM